2013
DOI: 10.5694/mja12.11407
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of the community‐level diet of Aboriginal people in remote northern Australia

Abstract: Very poor dietary quality continues to be a characteristic of remote Aboriginal community nutrition profiles since the earliest studies almost three decades ago. Significant proportions of key nutrients are provided from poor-quality nutrient-fortified processed foods. Further evidence regarding the impact of the cost of food on food purchasing in this context is urgently needed and should include cost-benefit analysis of improved dietary intake on health outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
125
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(133 citation statements)
references
References 12 publications
7
125
1
Order By: Relevance
“…Importantly, self-efficacy is considered the most important precursor to behaviour change (42) . In addition, by taking their meals home, they included the family unit into the food work processes, providing the family an opportunity to sample new and healthier foods and to discuss important factors such as cost, preferences, dietary patterns and habits (8)(9)(10)(11)(12)(13) that had the potential to influence dietary change, which is important in the prevention of nutritionrelated disease (40,43,44) . Compared with other countries of the world, Australia is classified as 'food secure' (45) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, self-efficacy is considered the most important precursor to behaviour change (42) . In addition, by taking their meals home, they included the family unit into the food work processes, providing the family an opportunity to sample new and healthier foods and to discuss important factors such as cost, preferences, dietary patterns and habits (8)(9)(10)(11)(12)(13) that had the potential to influence dietary change, which is important in the prevention of nutritionrelated disease (40,43,44) . Compared with other countries of the world, Australia is classified as 'food secure' (45) .…”
Section: Discussionmentioning
confidence: 99%
“…Barriers to healthy eating and food security among Australian Indigenous families have been attributed to poor nutritional knowledge and cooking skills, budgeting issues, high food prices, ease of access to convenience foods, poor access to nutritious foods and large household numbers (8)(9)(10)(11) . This has resulted in poor nutrition throughout the life span, causing inadequate consumption of proteins, carbohydrates, fats, minerals, vitamins and micronutrients, which are all essential in maintaining biological and physiological health (11)(12)(13) .…”
mentioning
confidence: 99%
“…Gray et al showed that women aged over 65 gained almost twice the muscle strength following exercise with omega III. Nutritional concerns, lack of availability of omega III rich foods may raise questions about the external validity of negative studies for the NT [86]. The proven agent Omacor is expensive and administrators will debate cost benefit.…”
Section: Beta Blockersmentioning
confidence: 99%
“…The data utilised in the present study were monthly food and beverage turnover figures for one year (including nutritional information) derived from electronic transaction data from all food providers in three very remote Indigenous communities in the Northern Territory, Australia (9) . A thorough description of the quality of the overall average intake derived from these data has been previously reported and discussed by Brimblecombe et al (9) .…”
Section: Overviewmentioning
confidence: 99%
“…from a 24 h diet recall during a survey) (8) or an average intake from a sustained period (e.g. from monthly food and beverage provider turnover) (9) . Although both of these approaches can provide valuable information about overall diet quality, they do not identify how it may fluctuate over short periods of extremes; for example, during an acute period (day/s) of reduced money availability.…”
Section: Overviewmentioning
confidence: 99%